Report on a collection of Mysidacea from South African off-shore and coastal waters (1957-59) and from Zanzibar. - - TATTERSALL, O.S. (Proc. Zool. Soc. London, 139: 221-247, 1962)
M712
M712; NeMys doc_id: 2991